Implementation of Incentive and Career Development of Performance with Motivation as an Intervening Variable - Jufrizen Jufrizen; Delyana Rahmawany Pulungan (Proceedings of AICS - Social Sciences, 2017)
The aim of this research is to find out how the influence of incentive, and career development on performance with motivation as the intervening variable. The population of this research is lecturers of University of Muhammadyah Sumatera Utara (UMSU). Sample which is taken from all faculties in UMSU so the total sample size used for this research was 300 respondents, taken by using accidental sampling method. The data was taken by questionnaire method and the data analysis method is using path analysis with SPSS. The results shows that (1) incentive has a significant relationship with motivation and performance of UMSU’s lecturers (2) career developments has an insignificant relationship with motivation and performance of UMSU’s lecturers (3) motivation act as an intervening variable which is mediating the relationship between incentive and career development with performance of UMSU’s lecturers.